2000
DOI: 10.1093/acprof:oso/9780195137071.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Managing Human Resources in the Human Services

Abstract: Managerial supervisors are those persons who supervise direct service staff, who oversee human service programs, and who perform macro practice tasks in their agencies on a daily basis. They are not clinical supervisors who oversee the treatment aspects of direct practice; nor are they administrators at the executive level. This book addresses the challenges facing the often under-appreciated managerial supervisors who oversee and provide a crucial organizational structure for work that occurs in human service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Duffield, 1992) or specific sectors (such as the public sector: e.g. Byrne and McHardy, 1999; Perlmutter et al, 2001), whilst some contributions either have an uncertain empirical foundation or are unashamedly prescriptive (Dixon, 1993; Peters, 1989; Weiss, 1998).…”
Section: The End Of Supervision? Organizational Change and ‘New’ Firsmentioning
confidence: 99%
“…Duffield, 1992) or specific sectors (such as the public sector: e.g. Byrne and McHardy, 1999; Perlmutter et al, 2001), whilst some contributions either have an uncertain empirical foundation or are unashamedly prescriptive (Dixon, 1993; Peters, 1989; Weiss, 1998).…”
Section: The End Of Supervision? Organizational Change and ‘New’ Firsmentioning
confidence: 99%
“…This definition emphasizes the leader's role in achieving the goal of the group or of the situation in which the leader acts. The leader sets the goals for the group, coordinates with its members in order to achieve the goals, and thus influences the group and its members in a given situation (Perlmutter et al, 2001).…”
Section: Views Of Leadership Throughout Historymentioning
confidence: 99%
“…acknowledged evaluations as positive feedback to improve performance, reduced turnover rate, increased employees motivation, increased feelings of equity among employees, and justifiable linkage between performance and rewards. Perlmutter and Bailey (2001) viewed provision of information for the development of managerial strategies for training and development as an outcome. Studies also found outcomes like reduced employee stress, review of overall progress, linkage between current performance and employee's goals, and development of specific action plans for future.…”
Section: Performance Appraisalmentioning
confidence: 99%